Through Bronfenbrenner’s Eyes: A look at Grade 1 teachers’ attempts at implementing a Reading Instruction Program - Fontejon Bonior, Gina A. (Silliman Journal, 2022)
This study investigates how Grade 1 teachers who are enacting a Reading Instruction Program in remote island communities in Central Philippines navigate through the complexities of program implementation in their local contexts using Bronfenbrenner’s bioecological systems theory (1979) and his Process–Person–Context–Time Model (1989). Narratives generated from eight Grade 1 teachers showed various strategies employed to effectively exercise their agency within the “complex reciprocal interaction” (Bronfenbrenner & Morris, 1998) among the various layers of interrelated systems (biological, micro-, meso-, exo-, and macro-) within a period of dynamic curricular changes in the Philippines; the K-12 reform initiative. The findings also suggest that, despite the various structural constraints that impact teacher enactment of the program, teachers find creative ways to position themselves socially and politically to contextualize the program and meet their goal: to make each child a reader in the mother tongue by the end of Grade 1. Findings suggest that, in these small island communities, such commitment is driven by a deep faith in God, who they believe is the author of the many privileges they are enjoying and who would eventually hold them accountable for the children in their care. On the other hand, such commitment may be driven by socioeconomic interests in that failure of students may result to high dropout rate, which in remote island communities with small student population may result in the closure of the school. This consequence may not be in the best interest not only of the community but also of the teachers themselves.